The effect of type of delivery on the nitric oxide metabolites and endothelial dysfunction in pregnant women - Maedeh Mojiri; Maryam Kianpour; Mehdi Nematbakhsh; Parvin Bahadoran (Wolters Kluwer Medknow Publications, 2020)
Background: Since endothelial dysfunction is related to atherosclerosis, this study was planned to determine the effect of type of delivery on Nitric Oxide (NO) metabolites and endothelial function. Materials and Methods: This Cohort study was conducted in 2015 in selected hospitals of Isfahan. 88 nulliparous women with gestational age of 39 weeks and above were enrolled in this study using convenience sampling method and finally, after giving birth, 51 mothers with vaginal delivery, 21 with urgent C-section and 13 with elective C-section were considered for data analysis. The serum levels of NO metabolites were measured in the laboratory with standard kits and data was analyzed using student and paired t-test, one-way ANOVA, and Chi-square test. The significance level was considered less than 0.05 for all tests. Results: The NO metabolites levels in mothers who had vaginal delivery or urgent C-section showed a significant difference before and after delivery (normal vaginal delivery (NVD): t50 = 5.61, p < 0.001, Urgent C-section: t23 = 5.38, p < 0.001). But those with elective C-section showed no significant difference in the nitrate and total nitrite levels before and after delivery (p > 0.05). Conclusions: Since reduction in serum levels of NO metabolites may possibly indicate endothelial dysfunction and predict cardiovascular disease, especially atherosclerosis in the future, it could be concluded that, childbirth, regardless of the type of delivery, could damage the endothelial cells but C-section (urgent or elective) could cause more disruption than vaginal delivery.